(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The present study includes a bibliometric analysis on the Internet of Things and smart cities. The objective of this work was to carry out a bibliometric review, highlighting an analysis of country networks, co-authorship, universities and number of documents that address the topics. Therefore, it is characterized as an exploratory study with a quantitative and qualitative nature, with data extracted from the Scopus database. The results allowed us to identify a bibliometric network with 3,575 documents, indicating that 99 documents are Brazilian productions. As a main conclusion, it was found that interest in the themes is growing.